Keystroke Dynamics Authentication based on Naïve Bayes Classifier - M. Hoobi, Mays (Iraqi Journal of Science, 2023)
Authentication is the process of determining whether someone or something is,in fact, who or what it is declared to be. As the dependence upon computers andcomputer networks grows, the need for user authentication has increased. User’sclaimed identity can be verified by one of several methods. One of the most popularof these methods is represented by (something user know), such as password orPersonal Identification Number (PIN). Biometrics is the science and technology ofauthentication by identifying the living individual’s physiological or behavioralattributes. Keystroke authentication is a new behavioral access control system toidentify legitimate users via their typing behavior. The objective of this paper is toprovide user authentication based on keystroke dynamic in order to avoid unauthorized user access to the system. Naive Bayes Classifier (NBC) is applied forkeystroke authentication using unigraph and diagraph keystroke features. Theunigraph Dwell Time (DT), diagraph Down-Down Time (DDT) features, andcombination of (DT and DDT) are used. The results show that the combination offeatures (DT and DDT) produces better results with low error rate as comparedwith using DT or DDT alone.